The impact of market orientation, top management support, use of e-marketing and technological opportunism on the firm performance: a mediated-moderation and moderated-mediation analysis - Sheikh, Adnan Ahmed; Shahzad, Arfan; Ku Ishak, Awanis (AJSS, 2017)
Understanding the effective use of technological innovation’s, for instance eMarketing, is debatably considered as the vital challenge faced by the businesses. The past studies indicated that the association among organizational factors and firm performance is mediated by the influence of the adopted innovation like e-Marketing uses. Though, the antecedents of e-Marketing to enhance firm performance have received little attention. Drawing on the Resource Based View and diffusion of innovation theory, this article has empirically examined the effect of Market Orientation (MO), top management support (TMS), Technological Opportunism (TOP) and mediating effect of use of e-Marketing (UEM) on textile performance by using SmartPLS 3.0 with a sample size of 278 textile firms in Pakistan. A moderated mediation analysis revealed that the relationship between MO and UEM is moderated by top management support and the mediated moderation analysis revealed that technological opportunism moderates the relationship between use of eMarketing and performance of textile firms. The direct hypothesis also found significant showing the positive relationships. Implications for theory and practice are discussed regarding bundling of IV and moderators in order to increase both UEM and firm performance.